PENGETAHUAN, SIKAP DAN PERILAKU MASYARAKAT DALAM PENCEGAHAN DEMAM DENGUE DI DESA KAWASI HALMAHERA SELATAN - Nachrawy, Tuthanurani; Hakim Husen, Abd; Do Toka, Wahyunita (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Dengue hemorrhagic fever (DHF) is a viral infectious disease that the Aedes aegypti mosquito spreads. South Halmahera Regency is one of the endemic areas for DHF in North Maluku Province. Data from the South Halmahera Regency Health Office reveals DHF data for January-April 2024. According to the data, the cause of the disease is mosquito bites, and it has reached 26 cases. Children dominate the sufferers. The incidence of DHF can be reduced by breaking the chain of transmission of the DHF virus by improving the quality of environmental sanitation, reducing the population of Aedes Aegypti mosquitoes as vectors of DHF and preventing it. This study aims to investigate the community's knowledge, attitudes, and behaviour regarding DHF prevention, highlighting the need for increased awareness and proactive action. The research method, a descriptive study conducted in Kawasi Village, Central Halmahera Regency, was chosen for its ability to provide a comprehensive understanding of the community's perspectives on DHF prevention. This study involved 35 respondents selected through non-random purposive sampling with a cross-sectional approach